Zeolite‐Catalyzed Formaldehyde–Propylene Prins Condensation. Issue 23 (13th November 2017) - Vasiliadou, Efterpi S.; Gould, Nicholas S.; Lobo, Raul F.
Abstract: Prins condensation of formaldehyde with propylene to form 3‐buten‐1‐ol is investigated using microporous solid acid catalysts. Zn/H‐beta shows high conversion but leads to a broad product distribution composed primarily of pyrans. Mechanistic studies revealed that 3‐buten‐1‐ol reacts via Prins cyclization or dehydrate to 1, 3‐butadiene that further reacts with formaldehyde via a hetero‐Diels–Alder reaction. These secondary reactions are suppressed over ZSM‐5 catalysts: 3‐buten‐1‐ol is the predominant product over H‐ZSM‐5 zeolite under all conditions investigated. 3‐Buten‐1‐ol selectivity of up to 75 % is achieved. In a second step 3‐buten‐1‐ol dehydrates at temperatures as low as 423 K, forming 1, 3‐butadiene. Although Brønsted acid sites are the primary catalytic sites, ion exchange of Zn II increases the overall rate and 3‐buten‐1‐ol selectivity. H‐ZSM‐5 showed significant differences in reactivity and selectivity as a function of the Si/Al ratio; optimal catalytic properties were observed within Si/Al=40–140. Abstract : Substituting homogenous acids : Prins condensation between formaldehyde and propylene is traditionally catalyzed by homogeneous acids. The first experimental evidence is reported of the reaction over microporous solid acid catalysts. It was determined that H‐ZSM‐5 (MFI) is the optimal catalyst favoring selective formation of 3‐buten‐1‐ol. In a second step, 3‐buten‐1‐ol easily dehydrates to 1, 3‐butadiene.